Relationship between entrepreneur human capital and employer attractiveness in recruitment - Zhang, Hao (2021)
Recruiting top talents has always been challenging for startup ventures. It is suggested that job seekers may not view working in a startup as attractive as working in an established firm for various reasons. Previous studies have suggested that entrepreneur's human capital is positively related to employer attractiveness. My study is built on previous studies and examined the relationship between individual human capital attributes and startup employer attractiveness, among two groups of students. A quantitative research method was deployed. The result of my study unable to find a significant relationship between employer attractiveness and entrepreneur's human capital. But the result suggests a significant difference in startup employer attractiveness between native students and foreign students.